Composite solid electrolyte, all-solid-state flexible lithium ion battery and preparation method

By adopting a composite solid electrolyte with coaxial fiber structure in solid-state lithium-ion batteries and combining electrospinning technology, the shortcomings in the battery in terms of flexibility and mechanical properties are solved, and a high energy density and safe and reliable all-solid flexible lithium-ion battery is achieved. .

CN119495799APending Publication Date: 2025-02-21SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311021066.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing solid-state lithium-ion batteries have shortcomings in flexibility and mechanical properties, which are prone to fall off of active substances and puncture of electrodes during bending and folding, affecting the safety and life of the battery.

Method used

The composite solid electrolyte with a coaxial fiber structure is adopted, and the garnet-type solid electrolyte is combined with the polymer electrolyte through electrospinning technology to form a network film structure to improve the flexibility and chemical stability of the electrolyte.

Benefits of technology

A fully solid state flexible lithium-ion battery with high energy density and safe and reliable is realized, which improves the mechanical properties and electrochemical stability of the battery and reduces the complexity of battery assembly and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495799A_ABST
    Figure CN119495799A_ABST
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte, which comprises one or more fibers having a coaxial structure, the fibers comprise a shell fiber and an inner core fiber, the shell fiber and the inner core fiber are coaxially arranged, at least a part of the inner core fiber is coated by the shell fiber, the shell fiber comprises a polymer electrolyte, and the polymer electrolyte is a polymer electrolyte. The inner core fiber comprises garnet type solid electrolyte. The composite solid electrolyte can be prepared by a coaxial electrostatic spinning method and comprises fibers with a coaxial structure, and an inorganic garnet type solid electrolyte sensitive to air is wrapped in a polymer electrolyte, so that the chemical stability of the composite solid electrolyte is more excellent; and the high efficiency of lithium ion transmission is further ensured. In addition, by means of the composite solid electrolyte, a safe and reliable all-solid-state flexible lithium ion battery with high energy density can be prepared through an electrostatic spinning technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid-state lithium batteries, and in particular to a composite solid-state electrolyte, an all-solid-state flexible lithium-ion battery and a preparation method thereof. Background Art

[0002] The rapid development of energy storage and conversion technology has led to the widespread use of various electrochemical devices such as lead-acid batteries, nickel-cadmium batteries, fuel cells, zinc-manganese batteries and lithium-ion batteries. Lithium-ion batteries (LIBs) have become the market leader due to their excellent specific energy, specific power density, long cycle life and environmental friendliness, and have played a significant role in the fields of mobile phones, portable computers, electric vehicles, grid energy storage, implantable medical devices and aerospace. Common traditional lithium-ion batteries use liquid electrolytes, which often have serious safety problems such as dendrite growth and leakage during use, and their energy density has been difficult to meet the needs of large-scale power equipment such as new energy vehicles. Compared with liquid electrolytes, solid-state lithium-ion batteries use solid electrolytes (SSEs) with the following advantages: First, they can inhibit dendrite growth and avoid leakage to improve safety; second, they can be used with lithium metal negative electrodes to achieve higher energy density; third, they play the role of diaphragms, making battery assembly more convenient and efficient, effectively reducing production costs; fourth, after being made thin and lightweight, the degree of flexibility can be significantly improved, and it is expected to prepare flexible batteries. Based on the above advantages, solid-state lithium-ion batteries are considered to be one of the most promising energy storage systems.

[0003] Organic-inorganic composite solid electrolytes are composed of organic polymers and inorganic substances. They combine the advantages of polymer electrolytes, such as processability and excellent interface contact, and inorganic ceramic electrolytes, such as high ionic conductivity and wide electrochemical window, and have attracted much attention. As a representative of garnet-type inorganic solid electrolytes, lithium lanthanum zirconium oxide Li7La3Zr2O 12(LLZO) has attracted much attention due to its good chemical stability to lithium metal, high room temperature ionic conductivity and wide electrochemical window, but its sensitivity to air leads to poor interfacial compatibility with electrode materials and large mass, which brings challenges to energy density. LLZO usually has two crystal structures, cubic phase and tetragonal phase, and the room temperature ionic conductivity of the former is twice that of the latter. Doping substitution of various elements can effectively stabilize the cubic phase structure, thereby improving the room temperature ionic conductivity. Polymer electrolytes have better flexibility and elasticity, can achieve close contact with electrodes, and are conducive to the interfacial transmission of ions, but they have disadvantages such as low room temperature ionic conductivity, narrow electrochemical window, and low lithium ion migration number. Therefore, it is the focus of research for technicians in this field to prepare a composite solid electrolyte with high ionic conductivity and excellent interfacial performance by compounding the garnet-type solid electrolyte LLZO modified by element doping with a common polymer matrix. At present, there is research on dispersing garnet-type solid electrolytes in polymer matrices to prepare organic-inorganic composite solid electrolytes.

[0004] At present, all-solid-state flexible batteries are facing great demand in the market due to their advantages such as light weight, high energy density, and portability and wearability. Flexible batteries not only have higher requirements on the electrochemical properties of energy storage devices, but also have more stringent requirements on mechanical properties such as bending and deformation of devices. For traditional electrode materials, powdered active substances are made into slurry with conductive materials and binders and coated on the current collector. During the bending and folding process of the battery, the active substances may fall off, and the electrodes may be punctured, causing the battery to short-circuit. Therefore, flexible batteries not only need to be improved in terms of solid electrolyte materials, but also need further innovative research in terms of electrode materials and battery structures. The preparation of flexible structure lithium batteries is also an important research direction for technicians in this field. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, an object of the present invention is to provide an improved composite solid electrolyte with a coaxial fiber structure, which combines the advantages of inorganic solid electrolytes and solid polymer electrolytes, has good electrochemical properties and flexibility, and can be folded and bent.

[0006] In a first aspect, the present invention provides a composite solid electrolyte, comprising one or more fibers having a coaxial structure, wherein the fibers include an outer shell fiber and an inner core fiber, and the outer shell fiber and the inner core fiber are coaxially arranged; wherein at least a portion of the inner core fiber is coated by the outer shell fiber, the outer shell fiber includes a polymer electrolyte, and the inner core fiber includes a garnet-type solid electrolyte.

[0007] In one embodiment, a plurality of fibers with a coaxial structure form a mesh structure, so that the composite solid electrolyte is in the form of a film. In one embodiment, the thickness of the film is preferably in the range of 20-30 microns.

[0008] In one embodiment, the mass percentage of the garnet-type solid electrolyte in the composite solid electrolyte is 20 wt % to 60 wt %.

[0009] In one embodiment, the garnet-type solid electrolyte is a lithium lanthanum zirconium oxide (LLZO) garnet-type solid electrolyte. In one embodiment, the molar ratio of lithium, lanthanum and zirconium in the lithium lanthanum zirconium oxide garnet-type solid electrolyte is 5:3:2 to 8:3:2.

[0010] In one embodiment, the polymer electrolyte is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

[0011] In one embodiment, the garnet-type solid electrolyte is further doped with a small amount of element, and the small amount of element is selected from at least one of aluminum, tantalum, gallium, niobium, strontium, calcium, iron, cerium, yttrium, germanium, molybdenum and tungsten.

[0012] In a second aspect, the present invention provides a method for preparing the composite solid electrolyte, which is prepared by coaxial electrospinning, comprising the following steps:

[0013] Preparation of garnet-type solid electrolytes by electrospinning;

[0014] Dissolving a first polymer electrolyte in a first solvent, and adding the garnet-type solid electrolyte to prepare a first spinning precursor solution;

[0015] dissolving a second polymer electrolyte in a second solvent to prepare a second spinning precursor solution;

[0016] The composite solid electrolyte is prepared by a coaxial electrospinning method, wherein the first spinning precursor solution is used as a coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as a coaxial electrospinning outer layer solution.

[0017] The steps of preparing the first spinning precursor solution and preparing the second spinning precursor solution are not in any particular order and can be performed simultaneously or at different times.

[0018] In one embodiment, in the step of preparing the first spinning precursor solution, the mass ratio of the garnet-type solid electrolyte to the first polymer electrolyte is 6:1 to 20:1.

[0019] In one embodiment, the first solvent and / or the second solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol and isopropanol.

[0020] In one embodiment, the first solvent and the second solvent are the same.

[0021] In one embodiment, the first solvent and the second solvent are different.

[0022] In one embodiment, the first polymer electrolyte and / or the second polymer electrolyte is / are selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

[0023] In one embodiment, the first polymer electrolyte and the second polymer electrolyte are the same.

[0024] In one embodiment, the first polymer electrolyte and the second polymer electrolyte are different.

[0025] In one embodiment, the injection flow rate ratio of the coaxial electrospinning inner layer solution to the coaxial electrospinning outer layer solution is 1:3 to 1:1.

[0026] In one embodiment, the parameters of the coaxial electrospinning method are as follows: the total injection flow rate of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is 0.36mL / h~2.4mL / h, the spinning voltage is 10kV~30kV, the rotation speed of the receiving device is 50r / min~100r / min, and the distance between the spinning needle and the receiving device is 10cm~15cm.

[0027] In one embodiment, the steps of preparing a garnet-type solid electrolyte include:

[0028] Dissolving a binder, a lithium source, a lanthanum source and a zirconium source in a third solvent and mixing them evenly to obtain a third spinning precursor solution;

[0029] Setting electrospinning parameters to obtain a garnet-type solid electrolyte precursor on a receiving device;

[0030] The garnet-type solid electrolyte precursor is sintered at 500° C. to 800° C. to obtain the garnet-type solid electrolyte.

[0031] In one embodiment, the third solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol and isopropanol.

[0032] In one embodiment, the molar ratio of the lithium source, the lanthanum source and the zirconium source is 5:3:2 to 8:3:2.

[0033] In one embodiment, the mass ratio of the binder to the total mass of the lithium source, the lanthanum source and the zirconium source is 4:15 to 1:2.

[0034] In one embodiment, the binder is selected from at least one of polyvinyl pyrrolidone, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate, polymethyl methacrylate, polyimide and polyether sulfone ketone.

[0035] In one embodiment, the lithium source is selected from at least one of lithium hydroxide, lithium perchlorate, lithium carbonate, lithium acetate, lithium nitrate and lithium chloride.

[0036] In one embodiment, the lanthanum source is selected from at least one of lanthanum oxide, lanthanum hydroxide, lanthanum chloride, lanthanum acetylacetonate, lanthanum acetate, and lanthanum nitrate.

[0037] In one embodiment, the zirconium source is selected from at least one of zirconium oxide, zirconium carbonate, zirconium oxynitrate, zirconium nitrate, zirconium acetate, zirconium tetrachloride and zirconium oxychloride.

[0038] In one embodiment, the garnet-type solid electrolyte is further doped with a small amount of element, and the small amount of element is selected from at least one of aluminum, tantalum, gallium, niobium, strontium, calcium, iron, cerium, yttrium, germanium, molybdenum and tungsten.

[0039] In one embodiment, the electrospinning parameters are as follows: spinning voltage 10 kV to 30 kV, injection flow rate 0.18 mL / h to 0.6 mL / h, the distance between the needle and the receiving device is 10 cm to 15 cm, and the rotation speed of the receiving device is 50 r / min to 100 r / min.

[0040] In one embodiment, the sintering time in step c is 2 to 3 hours.

[0041] Another object of the present invention is to provide a high energy density, safe and reliable all-solid-state flexible lithium-ion battery, which is prepared by electrospinning technology using the above-mentioned composite solid electrolyte.

[0042] In a third aspect, the present invention provides a method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0043] Preparation of all-solid-state flexible lithium-ion battery cathode materials by electrospinning using composite solid electrolytes:

[0044] The positive electrode active material of the lithium-ion battery, the carbon material, the composite solid electrolyte and the fourth polymer electrolyte are dissolved in a fourth solvent to prepare a fourth spinning precursor solution; the electrostatic spinning parameters are set and a carbon-based flexible material is set on a receiving device as a positive electrode current collector to receive the spinning, so as to obtain an all-solid-state flexible lithium-ion battery positive electrode material;

[0045] Preparation of all-solid-state flexible lithium-ion battery anode materials by electrospinning using composite solid electrolytes:

[0046] The negative electrode active material of the lithium-ion battery, the fifth polymer electrolyte, and the composite solid electrolyte are dissolved in the fifth solvent to prepare a fifth spinning precursor solution; the electrostatic spinning parameters are set and a carbon-based flexible material is set on the receiving device as a negative electrode current collector to receive the spinning, so as to obtain an all-solid-state flexible lithium-ion battery negative electrode material;

[0047] The all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte, and the all-solid-state flexible lithium-ion battery negative electrode material are assembled into a battery to obtain the all-solid-state flexible lithium-ion battery.

[0048] Among them, the steps of preparing the positive electrode material of the all-solid-state flexible lithium-ion battery and the negative electrode material of the all-solid-state flexible lithium-ion battery are not in a particular order and can be performed simultaneously or at different times.

[0049] In one embodiment, the mass ratio of the lithium ion battery positive electrode active material, the composite solid electrolyte, the carbon material and the fourth polymer electrolyte is: (4-8): (0.1-2.1): (0.1-0.5): (0.2-1).

[0050] In one embodiment, the mass ratio of the negative electrode active material of the lithium ion battery, the composite solid electrolyte and the fifth polymer electrolyte is: (3-7): (0.3-1.5): (0.1-0.7).

[0051] In one embodiment, the positive electrode active material of the lithium-ion battery is selected from at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide and nickel-cobalt-manganese ternary material. Nickel-cobalt-manganese ternary material is a battery positive electrode material made of nickel salt, cobalt salt and manganese salt as raw materials, and is made by mixing the three elements of nickel, cobalt and manganese in different proportions.

[0052] In one embodiment, the carbon material is selected from at least one of graphite and activated carbon.

[0053] In one embodiment, the negative electrode active material of the lithium ion battery is selected from at least one of graphite, silicon carbon, hard carbon and nano silicon material.

[0054] In one embodiment, the carbon-based flexible material comprises carbon fiber cloth.

[0055] In one embodiment, the fourth solvent and / or the fifth solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol, and isopropanol.

[0056] In one embodiment, the fourth solvent and the fifth solvent are the same.

[0057] In one embodiment, the fourth solvent and the fifth solvent are different.

[0058] In one embodiment, the fourth polymer electrolyte and / or the fifth polymer electrolyte is / are selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

[0059] In one embodiment, the fourth polymer electrolyte and the fifth polymer electrolyte are the same.

[0060] In one embodiment, the fourth polymer electrolyte and the fifth polymer electrolyte are different.

[0061] In one embodiment, the battery assembly is in the form of a button or soft pack.

[0062] In one embodiment, the electrospinning parameters are as follows: the injection flow rate is 0.18 mL / h to 0.6 mL / h, the spinning voltage is 10 kV to 30 kV, the rotation speed of the receiving device is 50 r / min to 100 r / min, and the distance between the spinning needle and the receiving device is 10 cm to 15 cm.

[0063] In a fourth aspect, the present invention provides an all-solid-state flexible lithium-ion battery, comprising an all-solid-state flexible lithium-ion battery positive electrode material, a composite solid electrolyte and an all-solid-state flexible lithium-ion battery negative electrode material;

[0064] The all-solid-state flexible lithium-ion battery positive electrode material comprises a positive electrode current collector and a positive electrode material, wherein the positive electrode material is attached to one side of the positive electrode current collector and is in direct contact with the composite solid electrolyte;

[0065] The all-solid-state flexible lithium-ion battery negative electrode material comprises a negative electrode current collector and a negative electrode material, wherein the negative electrode material is attached to one side of the negative electrode current collector and is in direct contact with the composite solid electrolyte;

[0066] The positive electrode current collector and the negative electrode current collector are made of carbon-based flexible materials.

[0067] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0068] 1. Compared with the prior art of dispersing garnet-type solid electrolytes in a polymer matrix, the composite solid electrolyte provided by the present invention includes fibers with a coaxial structure, and the air-sensitive inorganic garnet-type solid electrolyte is wrapped inside the polymer electrolyte. This structure not only makes the chemical stability of the composite solid electrolyte more excellent, but also further ensures the high efficiency of lithium ion transmission; in addition, the problem of large interface impedance of the existing solid electrolyte can be improved by utilizing the flexibility and elasticity of the polymer fiber membrane formed by the polymer electrolyte on the outer layer of the coaxial fiber structure.

[0069] 2. The organic-inorganic composite solid electrolyte provided by the present invention combines the advantages of polymer film processability, excellent interface contact, and high ionic conductivity and wide electrochemical window of inorganic garnet-type solid electrolytes, and can achieve efficient ion transport and is suitable for various electrochemical applications.

[0070] 3. The invention is the first to use coaxial electrospinning technology to introduce garnet-type solid electrolytes into a coaxial structure to prepare composite solid electrolytes. This innovative method has opened up a new path for the research and application of composite solid electrolytes and is expected to promote the further development of battery technology.

[0071] 4. The present invention provides a high energy density, safe and reliable all-solid-state flexible lithium-ion battery by utilizing a composite solid electrolyte, wherein both the positive and negative electrodes are flexible structures, thereby improving the interface contact between the positive and negative electrodes and the composite solid electrolyte, thereby improving the ionic conductivity.

[0072] 5. The composite solid electrolyte including fibers with a coaxial structure is mixed with electrode active materials through electrospinning technology to prepare flexible positive and negative electrodes, which further ensures the flatness and completeness of the solid-solid contact between the composite solid electrolyte and the positive and negative electrodes, thereby improving the structural flexibility and electrochemical reliability of the all-solid-state flexible lithium-ion battery.

[0073] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 is a schematic diagram of the composite solid electrolyte structure in one embodiment of the present invention;

[0075] Figure 2 is a flow chart of a method for preparing a composite solid electrolyte in one embodiment of the present invention;

[0076] Figure 3 is a flow chart of a method for preparing an all-solid-state flexible lithium-ion battery in one embodiment of the present invention;

[0077] Figure 4 is a schematic structural diagram of an all-solid-state flexible lithium-ion battery in one embodiment of the present invention;

[0078] Figure 5 Example 5 of the present invention at 20°C, 0.1 mA / cm 2 Figure 3. Stability test results in lithium symmetric cells at different current densities. DETAILED DESCRIPTION

[0079] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.

[0080] In the drawings, components with the same structure are indicated by the same numerical reference numerals, and components with similar structures or functions are indicated by similar numerical reference numerals. The size and thickness of each component shown in the drawings are arbitrarily shown, and the present invention does not limit the size and thickness of each component. In order to make the illustration clearer, the thickness of the components is appropriately exaggerated in some places in the drawings.

[0081] If not otherwise defined, any terms and scientific terms used herein are intended to have the meaning commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0082] In a first aspect, the present invention provides a composite solid electrolyte (such as Figure 1 As shown), the composite solid electrolyte includes one or more fibers with a coaxial structure, the fiber includes an outer shell fiber and an inner core fiber, and the outer shell fiber and the inner core fiber are coaxially arranged; wherein at least a portion of the inner core fiber is coated by the outer shell fiber, the outer shell fiber includes a polymer electrolyte, and the inner core fiber includes a garnet-type solid electrolyte.

[0083] In one embodiment, a plurality of fibers with a coaxial structure form a mesh structure, so that the composite solid electrolyte is in the form of a film. In one embodiment, the thickness of the film is preferably in the range of 20-30 microns.

[0084] In one embodiment, the mass proportion of the garnet-type solid electrolyte in the composite solid electrolyte is 20 wt % to 60 wt %.

[0085] In one embodiment, the garnet-type solid electrolyte is a lithium lanthanum zirconium oxide (LLZO) garnet-type solid electrolyte. In one embodiment, the molar ratio of lithium, lanthanum and zirconium in the lithium lanthanum zirconium oxide garnet-type solid electrolyte is 5:3:2 to 8:3:2.

[0086] In one embodiment, the polymer electrolyte is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

[0087] In one embodiment, the garnet-type solid electrolyte is further doped with a small amount of elements, and the small amount of elements is selected from at least one of aluminum, tantalum, gallium, niobium, strontium, calcium, iron, cerium, yttrium, germanium, molybdenum and tungsten.

[0088] In a second aspect, the present invention provides a method for preparing the composite solid electrolyte, such as Figure 2 As shown, the following steps are included:

[0089] Step 1, preparing a garnet-type solid electrolyte by electrospinning;

[0090] Step 2, dissolving the first polymer electrolyte in the first solvent, adding the garnet-type solid electrolyte, and preparing a first spinning precursor solution;

[0091] Step 3, dissolving the second polymer electrolyte in the second solvent to prepare a second spinning precursor solution;

[0092] Step 4: preparing a composite solid electrolyte by coaxial electrospinning, wherein the first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution.

[0093] Electrospinning is a technology for preparing nanofibers. This technology is usually carried out on a spinning machine, which usually consists of a charged ejector and a receiver. The basic principle is that under the action of an electric field, a polymer solution or molten polymer is ejected from the tip or nozzle of the ejector to form a thin and long fiber. When the polymer solution passes through the ejector, its surface charge is affected by the electric field and the charge is separated to form a conical droplet. When the electric field strength is large enough, the tip of the droplet will be electro-dropletized to form an extremely fine droplet, which eventually forms a continuous fiber.

[0094] Coaxial electrospinning is an improved electrospinning technology that allows other substances to be embedded inside the nanofibers to form fibers with a core-shell structure. This method uses two coaxially arranged ejectors, an internal ejector and an external ejector, to eject two different materials respectively. The basic principle of coaxial electrospinning is to eject the core material (inner layer solution) through the internal ejector, while the external ejector ejects the shell material (outer layer solution) around the core material. Under the action of the electric field, the two materials form a stable coaxial flow and form fibers at the tip of the ejector. Fibers with composite structures can be prepared by coaxial electrospinning.

[0095] The first solvent and the second solvent are preferably solvents having the following characteristics: ① soluble electrolyte; ② not reacting with electrolyte; ③ low boiling point, easy to evaporate during electrospinning. In one embodiment, the first solvent and / or the second solvent are selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol and isopropanol. In one embodiment, the first solvent and the second solvent are the same. In one embodiment, the first solvent and the second solvent are different.

[0096] The polymer electrolyte preferably has the following characteristics: ① ion conduction, electronic insulation; ② high lithium ion conductivity; ③ large electrochemical window. There is no special restriction on the molecular weight of the polymer electrolyte, and a molecular weight that is easily available on the market can be selected. When preparing the spinning precursor solution, the amount of polymer electrolyte and solvent can be adjusted according to actual conditions to meet the viscosity requirements of the spinning precursor solution. In addition to playing the role of electrolyte, the first and second polymer electrolytes are also used as binders for forming fibers. In one embodiment, the first polymer electrolyte and / or the second polymer electrolyte are selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl ethylene carbonate, polyvinyl carbonate and polymethyl methacrylate. In one embodiment, the first polymer electrolyte and the second polymer electrolyte are the same. In one embodiment, the first polymer electrolyte and the second polymer electrolyte are different.

[0097] In one embodiment, in step 2, the mass ratio of the garnet solid electrolyte to the first polymer electrolyte is 6:1 to 20:1.

[0098] In one embodiment, in step 4, the injection flow rate ratio of the coaxial electrospinning inner layer solution to the coaxial electrospinning outer layer solution is 1:3 to 1:1.

[0099] In one embodiment, step 2 is specifically as follows: dissolving the first polymer electrolyte in the first solvent, heating to 60-90°C, stirring and refluxing under the protection of an inert gas atmosphere until the solution is clarified, adding a garnet-type solid electrolyte, and stirring at room temperature for 8-12 hours to obtain a first spinning precursor solution.

[0100] In one embodiment, step 3 is specifically as follows: dissolving the second polymer electrolyte in the second solvent, heating to 60-90° C., stirring and refluxing under an inert gas atmosphere until the solution is clear, and then stirring at room temperature for 8-12 hours to obtain a second spinning precursor solution.

[0101] In one embodiment, the inert gas in step 2 and step 3 is Ar gas.

[0102] In one embodiment, the parameters of the coaxial electrospinning method in step 4 are as follows: the total injection flow rate of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is 0.36mL / h~2.4mL / h, the spinning voltage is 10kV~30kV, the rotation speed of the receiving device is 50r / min~100r / min, and the distance between the spinning needle and the receiving device is 10cm~15cm.

[0103] In one embodiment, step 1 includes the following steps:

[0104] Step a, dissolving a binder, a lithium source, a lanthanum source and a zirconium source in a third solvent, and mixing them evenly to obtain a third spinning precursor solution;

[0105] Step b, setting electrospinning parameters to obtain a garnet-type solid electrolyte precursor on a receiving device;

[0106] Step c: sintering the garnet-type solid electrolyte precursor at 500° C. to 800° C. to obtain a garnet-type solid electrolyte.

[0107] In one embodiment, the molar ratio of the lithium source, the lanthanum source and the zirconium source is 5:3:2 to 8:3:2.

[0108] In one embodiment, the mass ratio of the binder to the total mass of the lithium source, the lanthanum source and the zirconium source is 4:15 to 1:2.

[0109] In one embodiment, the third solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol and isopropanol.

[0110] The binder plays a "bonding" role in the electrospinning process and forms fibers. The binder will be burned during the sintering process in step c. In one embodiment, the binder is selected from at least one of polyvinyl pyrrolidone, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl ethylene carbonate, polyvinyl carbonate, polymethyl methacrylate, polyimide and polyether sulfone ketone.

[0111] In one embodiment, the lithium source is selected from at least one of lithium hydroxide, lithium perchlorate, lithium carbonate, lithium acetate, lithium nitrate and lithium chloride. In one embodiment, the lanthanum source is selected from at least one of lanthanum oxide, lanthanum hydroxide, lanthanum chloride, lanthanum acetylacetonate, lanthanum acetate and lanthanum nitrate. In one embodiment, the zirconium source is selected from at least one of zirconium oxide, zirconium carbonate, zirconium oxynitrate, zirconium nitrate, zirconium acetate, zirconium tetrachloride and zirconium oxychloride.

[0112] Doping a small amount of elements can improve the room temperature ionic conductivity of the garnet-type solid electrolyte. In one embodiment, the garnet-type solid electrolyte is further doped with a small amount of elements, and the small amount of elements is selected from at least one of aluminum, tantalum, gallium, niobium, strontium, calcium, iron, cerium, yttrium, germanium, molybdenum and tungsten.

[0113] In one embodiment, the electrospinning parameters in step b are as follows: spinning voltage 10kV~30kV, injection flow rate 0.18mL / h~0.6mL / h, the distance between the needle and the receiving device is 10cm~15cm, and the rotation speed of the receiving device is 50r / min~100r / min.

[0114] In one embodiment, the sintering time in step c is 2 to 3 hours.

[0115] Another object of the present invention is to provide a high energy density, safe and reliable all-solid-state flexible lithium-ion battery, which can be prepared by using the above-mentioned composite solid electrolyte and electrospinning technology.

[0116] In a third aspect, the present invention provides a method for preparing an all-solid-state flexible lithium-ion battery, such as Figure 3 As shown, the following steps are included:

[0117] Step S1, preparing an all-solid-state flexible lithium-ion battery positive electrode material by electrospinning:

[0118] The positive electrode active material of the lithium-ion battery, the carbon material, the composite solid electrolyte and the fourth polymer electrolyte are dissolved in a fourth solvent to prepare a fourth spinning precursor solution; the electrostatic spinning parameters are set and a carbon-based flexible material is set on a receiving device as a positive electrode current collector to receive the spinning, so as to obtain an all-solid-state flexible lithium-ion battery positive electrode material;

[0119] Step S2: preparing an all-solid-state flexible lithium-ion battery negative electrode material by electrospinning:

[0120] The negative electrode active material of the lithium-ion battery, the fifth polymer electrolyte, and the composite solid electrolyte are dissolved in the fifth solvent to prepare a fifth spinning precursor solution; the electrostatic spinning parameters are set and a carbon-based flexible material is set on the receiving device as a negative electrode current collector to receive the spinning, so as to obtain an all-solid-state flexible lithium-ion battery negative electrode material;

[0121] Step S3, assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0122] In one embodiment, in step S1, the mass ratio of the lithium-ion battery positive electrode active material, the composite solid electrolyte, the carbon material and the fourth polymer electrolyte is: (4-8): (0.1-2.1): (0.1-0.5): (0.2-1).

[0123] In one embodiment, in step S2, the mass ratio of the lithium-ion battery negative electrode active material, the composite solid electrolyte and the fifth polymer electrolyte is: (3-7): (0.3-1.5): (0.1-0.7).

[0124] The positive electrode active material of the lithium-ion battery adopts several commonly used positive electrode active materials. In one embodiment, the positive electrode active material of the lithium-ion battery is selected from at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide and nickel-cobalt-manganese ternary material. Nickel-cobalt-manganese ternary material is a battery positive electrode material made of nickel salt, cobalt salt and manganese salt as raw materials, and is made by mixing the three elements of nickel, cobalt and manganese in different proportions.

[0125] The carbon material mainly plays the role of conductivity. In one embodiment, the carbon material is selected from at least one of graphite and activated carbon.

[0126] The negative electrode active material of the lithium ion battery adopts several commonly used negative electrode active materials. In one embodiment, the negative electrode active material of the lithium ion battery is selected from at least one of graphite, silicon carbon, hard carbon and nano silicon material.

[0127] In one embodiment, the carbon-based flexible material comprises carbon fiber cloth.

[0128] The fourth solvent and the fifth solvent are preferably solvents having the following characteristics: ① soluble electrolyte; ② not reacting with electrolyte; ③ low boiling point, easy to evaporate during electrospinning. In one embodiment, the fourth solvent and / or the fifth solvent are selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol, and isopropanol. In one embodiment, the fourth solvent and the fifth solvent are the same. In one embodiment, the fourth solvent and the fifth solvent are different.

[0129] The fourth and fifth polymer electrolytes are preferably polymer electrolytes having the following characteristics: ① ion conduction, electronic insulation; ② high lithium ion conductivity; ③ large electrochemical window. In addition to playing the role of electrolyte, the fourth and fifth polymer electrolytes are also used as binders for forming fibers. There is no special restriction on the molecular weight of the polymer electrolyte, and a molecular weight that is easily available on the market can be selected. When preparing the spinning precursor solution, the amount of polymer electrolyte and solvent can be adjusted according to actual conditions to meet the viscosity requirements of the spinning precursor solution. In one embodiment, the fourth polymer electrolyte and / or the fifth polymer electrolyte are selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl ethylene carbonate, polyvinyl carbonate and polymethyl methacrylate. In one embodiment, the fourth polymer electrolyte and the fifth polymer electrolyte are the same. In one embodiment, the fourth polymer electrolyte and the fifth polymer electrolyte are different.

[0130] In one embodiment, the battery assembly in step S3 is in the form of a button type or a soft pack.

[0131] In one embodiment, the electrospinning parameters in step S1 or step S2 are as follows: the injection flow rate is 0.18 mL / h to 0.6 mL / h, the spinning voltage is 10 kV to 30 kV, the rotation speed of the receiving device is 50 r / min to 100 r / min, and the distance between the spinning needle and the receiving device is 10 cm to 15 cm.

[0132] In a fourth aspect, the present invention provides an all-solid-state flexible lithium-ion battery, Figure 4 It is a structural schematic diagram of an all-solid-state flexible lithium-ion battery, including an all-solid-state flexible lithium-ion battery positive electrode material 1, a composite solid electrolyte 2 and an all-solid-state flexible lithium-ion battery negative electrode material 3;

[0133] The all-solid-state flexible lithium-ion battery positive electrode material 1 comprises a positive electrode current collector 11 and a positive electrode material 12, wherein the positive electrode material 12 is attached to one side of the positive electrode current collector 11 and is in direct contact with the composite solid electrolyte 2;

[0134] The all-solid-state flexible lithium-ion battery negative electrode material 3 includes a negative electrode current collector 31 and a negative electrode material 32. The negative electrode material 32 is attached to one side of the negative electrode current collector 31 and is in direct contact with the composite solid electrolyte 2.

[0135] The composite solid electrolyte 2 includes an outer shell fiber 21 and an inner core fiber 22;

[0136] The positive electrode current collector 11 and the negative electrode current collector 31 are made of carbon-based flexible materials.

[0137] The all-solid-state flexible lithium-ion battery positive electrode material and the all-solid-state flexible lithium-ion battery negative electrode material provided by the present invention can exist as separate products before being assembled into an all-solid-state flexible lithium-ion battery.

[0138] In one embodiment, the all-solid-state flexible lithium-ion battery positive electrode material 1 includes a positive electrode current collector 11 and a positive electrode material 12, wherein the positive electrode material 12 is attached to one side of the positive electrode current collector 11.

[0139] The positive electrode material 12 includes a composite solid electrolyte; the positive electrode current collector 11 is a carbon-based flexible material.

[0140] In one embodiment, the all-solid-state flexible lithium-ion battery negative electrode material 3 includes a negative electrode current collector 31 and a negative electrode material 32, wherein the negative electrode material 32 is attached to one side of the negative electrode current collector 31.

[0141] The negative electrode material 32 includes a composite solid electrolyte; the negative electrode current collector 31 is a carbon-based flexible material.

[0142] Example

[0143] Example 1

[0144] A method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0145] (1) 1.6 g of polyvinyl pyrrolidone (PVP, Mw = 40,000) was dissolved in 30 mL of ethanol at room temperature and magnetically stirred for 2 h. A total of 18 g of lithium nitrate, lanthanum nitrate and zirconium nitrate were added in sequence according to the atomic ratio of Li:La:Zr = 7:3:2. The mixture was magnetically stirred for 2 h at room temperature to obtain a spinning precursor solution. Then, a garnet-type solid electrolyte (LLZO-type) precursor fiber was prepared by electrospinning, wherein the electrospinning parameters were set as follows: spinning voltage 30 kV, injection flow rate 0.3 mL / h, distance between the needle and the receiving device 15 cm, and speed of the receiving device 80 r / min. Finally, the LLZO precursor fiber was sintered at 800 °C for 2 h in an air atmosphere at a heating rate of 10 °C / min. Finally, a garnet-type solid electrolyte (LLZO-type) was received on a receiving device, which was in a fibrous state.

[0146] (2) 0.5 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 6 mL of N, N-dimethylformamide (DMF), and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, and then 6 g of garnet-type solid electrolyte (LLZO type) was added, and stirred at room temperature for 30 min to 60 min to make it uniformly mixed, and then magnetically stirred at room temperature for 8 h to obtain a uniformly mixed first spinning precursor solution;

[0147] (3) 0.6 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 5 mL of DMF, and refluxed under 80 °C Ar atmosphere with magnetic stirring until a clear transparent solution was obtained, and then stirred at room temperature for 8 h to obtain a second spinning precursor solution;

[0148] (4) The first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution. In the coaxial electrospinning process, the injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is set to 3:5, the total injection flow rate is 0.8 mL / h, the spinning voltage is 15 kV, the speed of the receiving device is 100 r / min, the distance between the spinning needle and the receiving device is 15 cm, and the composite solid electrolyte LLZO@PAN with a coaxial structure fiber is received on the receiving device, which is in the form of a thin film;

[0149] (5) 0.4 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 4.5 g lithium iron phosphate, 0.2 g activated carbon, and 0.5 g composite solid electrolyte LLZO@PAN were added, and stirred at room temperature for 30 min to 60 min to make them uniformly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.18 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery positive electrode material was received on the receiving device;

[0150] (6) 0.3 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 4 g silicon carbon and 0.5 g composite solid electrolyte LLZO@PAN were added, and stirred at room temperature for 30 min to 60 min to make it evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.18 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery negative electrode material was received on the receiving device;

[0151] (7) Assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte LLZO@PAN, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0152] Example 2

[0153] A method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0154] (1) 3 g of polyvinyl pyrrolidone (PVP, Mw = 40,000) was dissolved in 30 mL of ethanol at room temperature, and magnetically stirred for 2 h. A total of 40 g of lithium nitrate, lanthanum nitrate and zirconium nitrate were added in sequence according to the atomic ratio of Li:La:Zr = 7:3:2, and magnetically stirred for 2 h at room temperature to obtain a spinning precursor solution. Then, a garnet-type solid electrolyte (LLZO-type) precursor fiber was prepared by electrospinning, wherein the electrospinning parameters were set as follows: spinning voltage 30 kV, injection flow rate 0.3 mL / h, distance between the needle and the receiving device 15 cm, and speed of the receiving device 80 r / min. Finally, the above-mentioned LLZO precursor fiber was sintered at 800 ° C for 2 h in an air atmosphere, with a heating rate of 10 ° C / min, and finally a garnet-type solid electrolyte (LLZO-type) was received on the receiving device, which was in a fibrous state.

[0155] (2) 1 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 6 mL of N, N-dimethylformamide (DMF), and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 10 g of garnet-type solid electrolyte (LLZO type) was added, and stirred at room temperature for 30 min to 60 min to make it uniformly mixed, and then magnetically stirred at room temperature for 8 h to obtain a uniformly mixed first spinning precursor solution;

[0156] (3) 1.8 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 10 mL of DMF, and the mixture was refluxed and magnetically stirred at 80 °C under Ar atmosphere protection until a clear and transparent solution was obtained, and then stirred at room temperature for 8 h to obtain a second spinning precursor solution;

[0157] (4) The first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution. In the coaxial electrospinning process, the injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is set to 3:5, the total injection flow rate is 0.8 mL / h, the spinning voltage is 15 kV, the speed of the receiving device is 100 r / min, the distance between the spinning needle and the receiving device is 15 cm, and the composite solid electrolyte LLZO@PAN with a coaxial structure fiber is received on the receiving device, which is in the form of a thin film;

[0158] (5) 0.8 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 6.6 g lithium iron phosphate, 0.4 g graphite, and 1 g composite solid electrolyte LLZO@PAN were added, and stirred at room temperature for 30 min to 60 min to make them evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.18 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery positive electrode material was received on the receiving device;

[0159] (6) 0.6 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 6 g silicon carbon and 1.2 g composite solid electrolyte LLZO@PAN were added, and stirred at room temperature for 30 min to 60 min to make it evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.18 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery negative electrode material was received on the receiving device;

[0160] (7) Assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte LLZO@PAN, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0161] Example 3

[0162] A method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0163] (1) 1.6 g of polyvinyl pyrrolidone (PVP, Mw = 40,000) was dissolved in 30 mL of ethanol at room temperature and magnetically stirred for 2 h. A total of 18 g of lithium carbonate, lanthanum oxide, zirconium oxide and aluminum oxide were added in sequence according to the atomic ratio of Li: La: Zr: Al = 7.7: 3: 2: 0.2. The mixture was magnetically stirred for 2 h at room temperature to obtain a spinning precursor solution. Then, garnet-type solid electrolyte (LLZAO-type) precursor fibers were prepared by electrospinning, wherein the electrospinning parameters were set as follows: spinning voltage 25 kV, injection flow rate 0.5 mL / h, distance between needle and receiving device 15 cm, and speed of receiving device 80 r / min. Finally, the LLZAO precursor fibers were sintered at 500 °C for 3 h in an air atmosphere with a heating rate of 10 °C / min. Finally, the garnet-type solid electrolyte (LLZAO-type) was received on the receiving device, which was in the form of fibers.

[0164] (2) 0.5 g of polyethylene oxide (PEO, Mw = 600,000) was dissolved in 7 mL of N, N-dimethylformamide (DMF), and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 6 g of garnet-type solid electrolyte (LLZAO type) was added, and stirred at room temperature for 30 min to 60 min to make it uniformly mixed, and then magnetically stirred at room temperature for 8 h to obtain a uniformly mixed first spinning precursor solution;

[0165] (3) 0.6 g of polyethylene oxide (PEO, Mw = 600,000) was dissolved in 7 ml of DMF, and refluxed under 80 °C atmosphere with magnetic stirring until a clear transparent solution was obtained, and then stirred at room temperature for 8 h to obtain a second spinning precursor solution;

[0166] (4) The first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution. In the coaxial electrospinning process, the injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is set to 1:2, the total injection flow rate is 0.9 mL / h, the spinning voltage is 15 kV, the speed of the receiving device is 100 r / min, the distance between the spinning needle and the receiving device is 15 cm, and the composite solid electrolyte LLZAO@PEO with a coaxial structure fiber is received on the receiving device, which is in the form of a thin film;

[0167] (5) 0.3 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 5 g lithium cobalt oxide, 0.2 g activated carbon, and 0.3 g composite solid electrolyte LLZAO@PEO were added, and stirred at room temperature for 30 min to 60 min to make them uniformly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.2 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 100 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery positive electrode material was received on the receiving device;

[0168] (6) 0.2 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 4 g graphite and 0.4 g composite solid electrolyte LLZAO@PEO were added, and stirred at room temperature for 30 min to 60 min to make them uniformly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.2 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 100 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery negative electrode material was received on the receiving device;

[0169] (7) Assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte LLZAO@PEO, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0170] Example 4

[0171] A method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0172] (1) 3 g of polyvinyl pyrrolidone (PVP, Mw = 40,000) was dissolved in 30 mL of ethanol at room temperature and magnetically stirred for 2 h. A total of 40 g of lithium carbonate, lanthanum oxide, zirconium oxide and aluminum oxide were added in sequence according to the atomic ratio of Li: La: Zr: Al = 7.7: 3: 2: 0.2. The mixture was magnetically stirred for 2 h at room temperature to obtain a spinning precursor solution. Then, garnet-type solid electrolyte (LLZAO-type) precursor fibers were prepared by electrospinning, wherein the electrospinning parameters were set as follows: spinning voltage 25 kV, injection flow rate 0.5 mL / h, distance between needle and receiving device 15 cm, and speed of receiving device 80 r / min. Finally, the LLZAO precursor fibers were sintered at 500 °C for 3 h in an air atmosphere with a heating rate of 10 °C / min. Finally, the garnet-type solid electrolyte (LLZAO-type) was received on the receiving device, which was in the form of fibers.

[0173] (2) 1 g of polyethylene oxide (PEO, Mw = 600,000) was dissolved in 7 mL of N, N-dimethylformamide (DMF), and refluxed under 80 ° C Ar atmosphere with magnetic stirring until a clear and transparent solution was obtained, 10 g of garnet-type solid electrolyte (LLZAO type) was added, and stirred at room temperature for 30 min to make it uniformly mixed, and then magnetically stirred at room temperature for 8 h to obtain a uniformly mixed first spinning precursor solution;

[0174] (3) 1 g of polyethylene oxide (PEO, Mw = 600,000) was dissolved in 7 mL of DMF, and refluxed under 80 °C atmosphere with magnetic stirring until a clear transparent solution was obtained, and then stirred at room temperature for 8 h to obtain a second spinning precursor solution;

[0175] (4) The first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution. In the coaxial electrospinning process, the injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is set to 1:2, the total injection flow rate is 0.9 mL / h, the spinning voltage is 15 kV, the spinning is carried out at room temperature, the speed of the receiving device is 100 r / min, the distance between the spinning needle and the receiving device is 15 cm, and the composite solid electrolyte LLZAO@PEO with a coaxial structure fiber is received on the receiving device, which is in the form of a thin film;

[0176] (5) 0.6 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 7 g lithium cobalt oxide, 0.4 g activated carbon and 0.8 g composite solid electrolyte LLZAO@PEO were added, and stirred at room temperature for 30 min to make them evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.2 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 100 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery positive electrode material was received on the receiving device;

[0177] (6) 0.5 g PAN (Mw = 150,000) was dissolved in 7 mL DMF, and refluxed under 80 ° C Ar atmosphere protection with magnetic stirring until a clear and transparent solution was obtained, 6 g graphite and 1 g composite solid electrolyte LLZAO@PEO and were added, and stirred at room temperature for 30 min to make them uniformly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.2 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 100 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery negative electrode material was received on the receiving device;

[0178] (7) Assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte LLZAO@PEO, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0179] Example 5

[0180] A method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0181] (1) 1.6 g of polyvinyl pyrrolidone (PVP, Mw = 40,000) was dissolved in 30 mL of ethanol at room temperature and magnetically stirred for 2 h. A total of 18 g of lithium nitrate, lanthanum nitrate, zirconium nitrate and tantalum nitrate were added in sequence according to the atomic ratio of Li:La:Zr:Ta = 6.4:3:1.4:0.6. The mixture was magnetically stirred for 2 h at room temperature to obtain a spinning precursor solution. Then, a garnet-type solid electrolyte (LLZTO-type) precursor fiber was prepared by electrospinning, wherein the electrospinning parameters were set as follows: power supply voltage 25 kV, injection flow rate 0.6 mL / h, distance between the needle and the receiving device 15 cm, and speed of the receiving device 80 r / min. Finally, the LLZTO precursor fiber was sintered at 800 °C for 2 h in an air atmosphere at a heating rate of 10 °C / min. Finally, a garnet-type solid electrolyte (LLZTO-type) was received on a receiving device, which was in a fibrous state.

[0182] (2) 1 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 7 mL of N, N-dimethylformamide (DMF), and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, and 6 g of the prepared garnet-type solid electrolyte (LLZTO type) was added, and stirred at room temperature for 30 min to make it uniformly mixed, and then magnetically stirred at room temperature for 8 h to obtain a uniformly mixed first spinning precursor solution;

[0183] (3) 0.6 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 5 mL of DMF, and refluxed under 80 °C Ar atmosphere with magnetic stirring until a clear transparent solution was obtained, and then stirred at room temperature for 8 h to obtain a second spinning precursor solution;

[0184] (4) The first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution. In the coaxial electrospinning process, the injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is set to 2:3, the total injection flow rate is 0.5 mL / h, the spinning voltage is 15 kV, the speed of the receiving device is 80 r / min, the distance between the spinning needle and the receiving device is 15 cm, and the composite solid electrolyte LLZTO@PAN with a coaxial structure fiber is received on the receiving device, which is in the form of a thin film;

[0185] (5) 0.4 g PAN (Mw = 150,000) was dissolved in 8 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 4.5 g lithium iron phosphate, 0.2 activated carbon, and 1 g composite solid electrolyte LLZTO@PAN were added, and stirred at room temperature for 30 min to make them evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.3 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery positive electrode material was received on the receiving device;

[0186] (6) 0.3 g PAN (Mw = 150,000) was dissolved in 8 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 4 g graphite and 0.8 g composite solid electrolyte LLZTO@PAN were added, and stirred at room temperature for 30 min to make them evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.3 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery negative electrode material was received on the receiving device;

[0187] (7) Assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte LLZO@PAN, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0188] Example 6

[0189] A method for preparing an all-solid-state flexible lithium-ion battery, comprising the following steps:

[0190] (1) 3 g of polyvinyl pyrrolidone (PVP, Mw = 40,000) was dissolved in 30 mL of ethanol at room temperature, and magnetically stirred for 2 h. A total of 40 g of lithium nitrate, lanthanum nitrate, zirconium nitrate and tantalum nitrate were added in sequence according to the atomic ratio of Li: La: Zr: Ta = 6.4: 3: 1.4: 0.6, and magnetically stirred for 2 h at room temperature to obtain a spinning precursor solution. Then, a garnet-type solid electrolyte (LLZTO-type) precursor fiber was prepared by electrospinning, wherein the electrospinning parameters were set as follows: power supply voltage 25 kV, injection flow rate 0.6 mL / h, distance between the needle and the receiving device 15 cm, and speed of the receiving device 80 r / min. Finally, the above-mentioned LLZTO precursor fiber was sintered at 800 ° C for 2 h in an air atmosphere, with a heating rate of 10 ° C / min, and finally a garnet-type solid electrolyte (LLZTO-type) was received on the receiving device, which was in a fibrous state.

[0191] (2) 1 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 7 mL of N, N-dimethylformamide (DMF), and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, and 10 g of the prepared garnet-type solid electrolyte (LLZTO type) was added, and stirred at room temperature for 30 min to make it uniformly mixed, and then magnetically stirred at room temperature for 8 h to obtain a uniformly mixed first spinning precursor solution;

[0192] (3) 1.8 g of polyacrylonitrile (PAN, Mw = 150,000) was dissolved in 10 mL of DMF, and refluxed under 80 °C Ar atmosphere with magnetic stirring until a clear transparent solution was obtained, and then stirred at room temperature for 8 h to obtain a second spinning precursor solution;

[0193] (4) The first spinning precursor solution is used as the coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as the coaxial electrospinning outer layer solution. In the coaxial electrospinning process, the injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is set to 2:3, the total injection flow rate is 0.5 mL / h, the spinning voltage is 15 kV, the speed of the receiving device is 80 r / min, the distance between the spinning needle and the receiving device is 15 cm, and the composite solid electrolyte LLZTO@PAN with a coaxial structure fiber is received on the receiving device, which is in the form of a thin film;

[0194] (5) 0.8 g PAN (Mw = 150,000) was dissolved in 10 mL DMF, and the solution was refluxed and magnetically stirred at 80 ° C under Ar atmosphere protection until it became a clear and transparent solution, 6.6 g lithium iron phosphate, 0.4 g graphite, and 2 g composite solid electrolyte LLZTO@PAN were added, and the mixture was stirred at room temperature for 30 min to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.3 mL / h, the spinning voltage was set to 15 kV, the speed of the receiving device was set to 80 r / min, and the distance between the spinning needle and the receiving device was set to 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the positive electrode material of the all-solid-state flexible lithium-ion battery was obtained on the receiving device;

[0195] (6) 0.6 g PAN (Mw = 150,000) was dissolved in 10 mL DMF, and refluxed under 80 ° C Ar atmosphere protection and magnetically stirred until a clear and transparent solution was obtained, 6 g graphite and 1.4 g composite solid electrolyte LLZTO@PAN were added, and stirred at room temperature for 30 min to make them evenly mixed to obtain a spinning precursor solution; the injection flow rate during electrospinning was set to 0.3 mL / h, the spinning voltage was 15 kV, the speed of the receiving device was 80 r / min, and the distance between the spinning needle and the receiving device was 15 cm; a carbon fiber cloth current collector was set on the receiving device as a substrate, and the all-solid-state flexible lithium-ion battery negative electrode material was received on the receiving device;

[0196] (7) Assembling the all-solid-state flexible lithium-ion battery positive electrode material, the composite solid electrolyte LLZO@PAN, and the all-solid-state flexible lithium-ion battery negative electrode material to obtain an all-solid-state flexible lithium-ion battery.

[0197] Using the Blue Battery Test System at 20°C, 0.1 mA / cm 2 The stability of the all-solid-state flexible lithium-ion battery obtained in Example 5 was tested at a current density of Figure 5 As shown by Figure 5 It can be seen that the all-solid-state flexible lithium-ion battery has excellent stability.

[0198] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A composite solid electrolyte, characterized in that: The invention comprises one or more fibers having a coaxial structure, wherein the fibers comprise an outer shell fiber and an inner core fiber, and the outer shell fiber and the inner core fiber are coaxially arranged; wherein at least a portion of the inner core fiber is coated by the outer shell fiber, the outer shell fiber comprises a polymer electrolyte, and the inner core fiber comprises a garnet-type solid electrolyte.

2. The composite solid electrolyte according to claim 1, characterized in that A plurality of fibers with coaxial structures form a mesh structure.

3. The composite solid electrolyte according to claim 1, characterized in that The garnet-type solid electrolyte includes a lithium lanthanum zirconium oxygen garnet-type solid electrolyte; The polymer electrolyte is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

4. A method for preparing a composite solid electrolyte, characterized in that: The following steps are involved: Preparation of garnet-type solid electrolytes by electrospinning; Dissolving a first polymer electrolyte in a first solvent, and adding the garnet-type solid electrolyte to prepare a first spinning precursor solution; dissolving a second polymer electrolyte in a second solvent to prepare a second spinning precursor solution; The composite solid electrolyte is prepared by a coaxial electrospinning method, wherein the first spinning precursor solution is used as a coaxial electrospinning inner layer solution, and the second spinning precursor solution is used as a coaxial electrospinning outer layer solution.

5. The preparation method according to claim 4, characterized in that: The first solvent and / or the second solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol and isopropanol; The first polymer electrolyte and / or the second polymer electrolyte is / are selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

6. The preparation method according to claim 4, characterized in that: The injection flow rate ratio of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is 1:3 to 1:

1.

7. The preparation method according to claim 4, characterized in that: The parameters of the coaxial electrospinning method are as follows: the total injection flow rate of the coaxial electrospinning inner layer solution and the coaxial electrospinning outer layer solution is 0.36mL / h~2.4mL / h, the spinning voltage is 10kV~30kV, the rotation speed of the receiving device is 50r / min~100r / min, and the distance between the spinning needle and the receiving device is 10cm~15cm.

8. The preparation method according to claim 4, characterized in that: The steps of preparing a garnet-type solid electrolyte include: Dissolving a binder, a lithium source, a lanthanum source and a zirconium source in a third solvent and mixing them evenly to obtain a third spinning precursor solution; Setting electrospinning parameters to obtain a garnet-type solid electrolyte precursor on a receiving device; The garnet-type solid electrolyte precursor is sintered at 500° C. to 800° C. to obtain the garnet-type solid electrolyte.

9. The preparation method according to claim 8, wherein The third solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol and isopropanol; The binder is selected from at least one of polyvinyl pyrrolidone, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate, polymethyl methacrylate, polyimide and polyether sulfone ketone.

10. A method for preparing an all-solid-state flexible lithium-ion battery positive electrode material, characterized in that: The following steps are involved: The positive electrode active material of the lithium-ion battery, the carbon material, the composite solid electrolyte and the fourth polymer electrolyte are dissolved in a fourth solvent to prepare a fourth spinning precursor solution; the electrostatic spinning parameters are set and a carbon-based flexible material is set on a receiving device as a positive electrode current collector to receive the spinning to obtain an all-solid-state flexible lithium-ion battery positive electrode material; Wherein, the composite solid electrolyte is the composite solid electrolyte according to any one of claims 1 to 3 or the composite solid electrolyte prepared by the method according to any one of claims 4 to 9.

11. The method for preparing the all-solid-state flexible lithium-ion battery positive electrode material according to claim 10, characterized in that: The lithium-ion battery positive electrode active material is selected from at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide and nickel-cobalt-manganese ternary material; The carbon material is selected from at least one of graphite and activated carbon; The carbon-based flexible material includes carbon fiber cloth.

12. The method for preparing the all-solid-state flexible lithium-ion battery positive electrode material according to claim 10, characterized in that: The fourth solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol, and isopropanol; The fourth polymer electrolyte is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

13. The method for preparing the all-solid-state flexible lithium-ion battery positive electrode material according to claim 10, characterized in that: The electrospinning parameters are as follows: injection flow rate is 0.18 mL / h to 0.6 mL / h, spinning voltage is 10 kV to 30 kV, the rotation speed of the receiving device is 50 r / min to 100 r / min, and the distance between the spinning needle and the receiving device is 10 cm to 15 cm.

14. A method for preparing an all-solid-state flexible lithium-ion battery negative electrode material, characterized in that: The following steps are involved: Dissolving the lithium-ion battery negative electrode active material, the fifth polymer electrolyte, and the composite solid electrolyte in a fifth solvent to prepare a fifth spinning precursor solution; The electrospinning parameters are set and a carbon-based flexible material is arranged on a receiving device as a negative electrode current collector to receive the spinning, so that an all-solid-state flexible lithium-ion battery negative electrode material can be obtained; Wherein, the composite solid electrolyte is the composite solid electrolyte according to any one of claims 1 to 3 or the composite solid electrolyte prepared by the method according to any one of claims 4 to 9.

15. The method for preparing the all-solid-state flexible lithium-ion battery negative electrode material according to claim 14, characterized in that: The lithium-ion battery negative electrode active material is selected from at least one of graphite, silicon carbon, hard carbon and nano silicon material; The carbon-based flexible material includes carbon fiber cloth.

16. The method for preparing the all-solid-state flexible lithium-ion battery negative electrode material according to claim 14, characterized in that: The fifth solvent is selected from at least one of methanol, ethanol, N,N-dimethylformamide, tetrahydrofuran, acetic acid, ethylene glycol, and isopropanol; The fifth polymer electrolyte is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethylethylene carbonate, polyvinyl carbonate and polymethyl methacrylate.

17. The method for preparing the all-solid-state flexible lithium-ion battery negative electrode material according to claim 14, characterized in that: The electrospinning parameters are as follows: injection flow rate is 0.18 mL / h to 0.6 mL / h, spinning voltage is 10 kV to 30 kV, the rotation speed of the receiving device is 50 r / min to 100 r / min, and the distance between the spinning needle and the receiving device is 10 cm to 15 cm.

18. An all-solid-state flexible lithium-ion battery positive electrode material, characterized in that: The invention comprises a positive electrode current collector and a positive electrode material, wherein the positive electrode material is attached to one side of the positive electrode current collector. Wherein, the positive electrode material comprises a composite solid electrolyte according to any one of claims 1 to 3 or a composite solid electrolyte prepared by the method according to any one of claims 4 to 9; The positive electrode current collector is a carbon-based flexible material.

19. An all-solid-state flexible lithium-ion battery negative electrode material, characterized in that: The invention comprises a negative electrode current collector and a negative electrode material, wherein the negative electrode material is attached to one side of the negative electrode current collector. Wherein, the negative electrode material comprises a composite solid electrolyte according to any one of claims 1 to 3 or a composite solid electrolyte prepared by the method according to any one of claims 4 to 9; The negative electrode current collector is a carbon-based flexible material.

20. An all-solid-state flexible lithium-ion battery, characterized in that: The all-solid-state flexible lithium-ion battery comprises an all-solid-state flexible lithium-ion battery positive electrode material, a composite solid electrolyte and an all-solid-state flexible lithium-ion battery negative electrode material; Wherein, the all-solid-state flexible lithium-ion battery positive electrode material is the all-solid-state flexible lithium-ion battery positive electrode material as claimed in claim 18, comprising a positive electrode current collector and a positive electrode material, wherein the positive electrode material is attached to one side of the positive electrode current collector and is in direct contact with the composite solid electrolyte; The all-solid-state flexible lithium-ion battery negative electrode material is the all-solid-state flexible lithium-ion battery negative electrode material as claimed in claim 19, comprising a negative electrode current collector and a negative electrode material, wherein the negative electrode material is attached to one side of the negative electrode current collector and is in direct contact with the composite solid electrolyte; The composite solid electrolyte is the composite solid electrolyte according to any one of claims 1 to 3 or the composite solid electrolyte prepared by the method according to any one of claims 4 to 9.